(untitled) (Journal of Oriental Studies, 2025)
This study analyzes changes in the spatial distribution of the rural population in post-Soviet Kazakhstan using census data from 1989 to 2024. While the total rural population has remained stable, over 27% of rural settlements have been eliminated during the sample period. Applying a proximity-based framework, the research shows that districts near major cities have experienced rural population growth and resilience, while remote areas face sharp decline and village abandonment. The findings reveal a selective spatial reorganization of the rural landscape, with populations concentrating in fewer, larger settlements located within accessible distance of major urban centers. These dynamics reflect not only rural decline, but also broader structural changes aligned with Kazakhstan’s ongoing urbanization. The observed patterns are closely tied to Kazakhstan’s broader urbanization process in a way that cities have become a key factor shaping rural viability, reinforcing demographic and spatial reorganization across the country. Overall, the findings align with broader research on rural transformation, providing a detailed case of how proximity to urban centers has shaped rural population patterns and settlement structures in post-Soviet Kazakhstan over time, reflecting enduring trends of spatial concentration and selective territorial development. Keywords: rural population, population geography, urbanization, migration, post-Soviet Kazakhstan.